2023
DOI: 10.26740/aluqud.v7n1.p33-53
|View full text |Cite
|
Sign up to set email alerts
|

Academic community's investment decision in sharia stock market: The impact of financial literacy

Abstract: This study aims to determine the impact of Islamic financial literacy on the academic community at IAIN Ambon in investing in the Islamic capital market. The research methodology uses interpretive qualitative techniques. Data were collected through observation and in-depth interviews with the academic community who became informants who were determined using the purposive sampling technique. The results of the study revealed that the academic community of IAIN Ambon has high financial literacy because they rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Hence, it can be observed that Generation Z possesses a comprehensive awareness of the Islamic capital market, enabling them to recognize the periodic fluctuations in Islamic stock values. Generation Z also has a good opportunity to make money by selling the stocks they have purchased at a profit when they anticipate a price drop (Holle et al, 2023). The increasing awareness of the importance of financial literacy has led to the development of educational programs from organizations such as the Financial Services Authority (OJK) and educational institutions such as universities to educate millennials that investing is not difficult and that anyone with access to the internet can do it.…”
Section: The Effect Of Islamic Capital Market Literacy On Investment ...mentioning
confidence: 99%
“…Hence, it can be observed that Generation Z possesses a comprehensive awareness of the Islamic capital market, enabling them to recognize the periodic fluctuations in Islamic stock values. Generation Z also has a good opportunity to make money by selling the stocks they have purchased at a profit when they anticipate a price drop (Holle et al, 2023). The increasing awareness of the importance of financial literacy has led to the development of educational programs from organizations such as the Financial Services Authority (OJK) and educational institutions such as universities to educate millennials that investing is not difficult and that anyone with access to the internet can do it.…”
Section: The Effect Of Islamic Capital Market Literacy On Investment ...mentioning
confidence: 99%